Non-tuberculous mycobacterial infection over abdomen: an interesting case report - Velapati, Sai Teja Reddy; Gopal, K. V. T.; Raju, P. V. Krishnam; Bulla, Rekha Rani (International Journal of Research in Dermatology, 2024)
Non‐tuberculous mycobacteria (NTM) are Mycobacterium species other than M. tuberculosis and M. leprae. - referred to as ‘atypical’. They are acid-fast bacilli residing in soil and water that cause cutaneous infections primarily after trivial trauma, surgery and cosmetic procedures. Skin and soft tissue infections (SSTI) caused by NTM species are increasing in incidence. They have a wide spectrum of clinical manifestations. NTM SSTI should be suspected when the skin infection does not respond to empirical antibiotics; Although, even with a sound clinical suspicion, the relatively low sensitivity of AFB & Fite staining as well as non-specific histopathology findings, the diagnosis is difficult. Optimal therapy is not well established, but usually is species dependent and includes use of multiple antibiotics for several months and potential use of adjunctive surgery. We report a case of 40-year-old female presented with chief complaint of multiple painful swellings over abdomen for 2 years not subsiding with standard antibiotic and surgical management. Investigations were done to rule out cutaneous tuberculosis, mycetoma and septic panniculitis; Automated mycobacterial culture on Modified Middlebrook 7H9 broth showed growth of NTM after 13 days of aerobic incubation. Though species could not be identified due to lack of resources, she was treated with combination of Rifampicin, Clarithromycin and Minocycline for 6 months; Good response was seen within 3 weeks and complete clearance of abscess was seen after 2 months of follow-up.